Biological conceptions and systems theory. A contextual and conceptual-theoretical study - Vázquez Pérez, Eduardo Daniel (2022)
For some it may be impossible, and even unacceptable, to think that biology is interconnected with the social sciences. For many others, it is a complement that allows us to understand the behavior of social subjects in their interaction with their partners in society, to the extent that the social system is integrated by functional communications. However, in order to understand the functioning of society from its complexity, it is important to take up again some previous elements that reveal that social subjects act through their internal communications, that is, their merely biological communications that have effects on their dynamics and interaction in society.